Gravimetric, electrochemical, and morphological studies of an isoxazole derivative as corrosion inhibitor for mild steel in 1M HCl - Jeenat Aslam; Ruby Aslam; Salhah Hamed Alrefaee; Mohammad Mobin; Afroz Aslam; Mehtab Parveen; Chaudhery Mustansar Hussain (Arabian Journal of Chemistry, 2020)
In present study, an isoxazole derivative, namely, (Z)-4-(4-hydroxy-3-methoxybenzylidene)-3-methylisoxazol-5(4H)-one referred here as (IOD) has been studied as an environment-friendly corrosion inhibitor for mild steel (MS) in acidic medium (1 M HCl). The present work was investigated by gravimetric, electrochemical impedance spectroscopy (EIS), potentiodynamic polarization (PDP), fourier-transform infrared (FT-IR) spectroscopy techniques. Atomic force microscopy (AFM), scanning electron microscopy (SEM), and energy-dispersive X-ray spectroscopy (EDS) confirmed the surface morphologies of the MS surface with and without IOD in the acid medium. The inhibition efficiency (I.E.) of IOD was increased by rising its concentration attaining maximum value (96.6%) at 300 ppm at 30 °C and decreases with increasing temperature from 30 °C to 60 °C. The adsorption of studied inhibitor followed Langmuir adsorption isotherm model. The PDP study revealed that the IOD acts as a mixed-type inhibitor with predominating anodic effect. The EIS study confirmed that increasing IOD concentration enhances the charge transfer resistance (Rct) and then reduces the double layer capacitance (Cdl) owing to the development of a protective layer on the MS surface.